Differences in crystalline cellulose modification due to degradation by brown and white rot fungi - Hastrup, Anne Christine Steenkjær; Howell, Caitlin (Fungal biology, 2012)
Wood-decaying basidiomycetes are some of the most effective bioconverters of lignocellulose in nature, however the way they alter wood crystalline cellulose on a molecular level is still not well understood. To address this, we examined and compared changes in wood undergoing decay by two species of brown rot fungi, Gloeophyllum trabeum and Meruliporia incrassata, and two species of white rot fungi, Irpex lacteus and Pycnoporus sanguineus, using X-ray diffraction (XRD) and 13C solid-state nuclear magnetic resonance (NMR) spectroscopy. The overall percent crystallinity in wood undergoing decay by M. incrassata, G. trabeum, and I. lacteus appeared to decrease according to the stage of decay, while in wood decayed by P. sanguineus the crystallinity was found to increase during some stages of degradation. This result is suggested to be potentially due to the different decay strategies employed by these fungi. The average spacing between the 200 cellulose crystal planes was signiﬁcantly decreased in wood degraded by brown rot, whereas changes observed in wood degraded by the two white rot fungi examined varied according to the selectivity for lignin. The conclusions were supported by a quantitative analysis of the structural components in the wood before and during decay conﬁrming the distinct differences observed for brown and white rot fungi. The results from this study were consistent with differences in degradation methods previously reported among fungal species, speciﬁcally more nonenzymatic degradation in brown rot versus more enzymatic degradation in white rot.
Gesehen am 11.09.2018